A Novel Anti-Histone H1 Monoclonal Antibody, SSV Monoclonal Antibody, Improves Lung Injury and Survival in a Mouse Model of Lipopolysaccharide-Induced Sepsis-Like Syndrome. (11th January 2015) - Kusano, Toru; Chiang, Kuei-Chen; Inomata, Masafumi; Shimada, Yayoi; Ohmori, Naoya; Goto, Takeshi; Sato, Shuji; Goto, Shigeru; Nakano, Toshiaki; Kawamoto, Seiji; Takaoka, Yuki; Shiraishi, Norio; et al.
Abstract : Background . Histones play important roles in both host defenses and inflammation related to microbial infection. A peptide mimotope (SSV) was identified from a novel histone H1 monoclonal antibody (16G9 mAb) that was shown to inhibit the mixed lymphocyte reaction. In the present study, an anti-SSV producing hybridoma was established. We investigated the effects of SSV mAb in a mouse acute inflammation model induced by intraperitoneal injection of lipopolysaccharide (LPS). Methods . SSV mAb was generated and characterized. Mice were treated with SSV mAb or a control IgG antibody prior to LPS injection. Evaluation of survival rate and lung tissue on histological score was performed. The levels of inflammatory cytokines and histones H1, H3, and H4 in plasma and lung tissue were measured by ELISA. Results . Competitive ELISA revealed that SSV mAb binds to histone H1. SSV mAb improved lung injury and prolonged the survival of LPS-injected mice. Increased levels of histones H1, H3, and H4 and inflammatory cytokines (TNF- α, IL-1 β, and IL-6) in plasma and lung tissue after LPS injection were ameliorated by SSV mAb. Conclusion . SSV mAb is shown to have anti-inflammatory activity and organ-protective effects, highlighting the importance of controlling histone H1 as well as H3 and H4 levels during inflammation.